2013
DOI: 10.1039/c2cp42766d
|View full text |Cite
|
Sign up to set email alerts
|

Local structure of ionic liquids probed by self-quenching of thiobenzophenone

Abstract: Self-quenching of the triplet excited state of thiobenzophenone ((3)TBP*) in molecular solvents, a sodium dodecyl sulfate (SDS) micellar solution, and ionic liquids (ILs) was measured using nanosecond laser flash photolysis. In the molecular solvents and ILs, (3)TBP* single-exponentially decayed, and the decay was accelerated with increasing TBP concentration. Self-quenching rate constants (k(SQ)) obtained in the ILs were smaller than those in the molecular solvents with similar solvent viscosities, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…We will briefly discuss the reason for the decrease in τ T as the motions of the molecules become more allowed. First, self-quenching (T 1 + S 0 → S 0 + S 0 ) among perylene molecules is not responsible for this behavior, and this is based on our experimental confirmation of τ T being independent of perylene concentration (Figure S6 in the Supporting Information). Generally, for a molecule to change its electronic spin state, a fluctuating time-dependent magnetic perturbation at the position of the molecule is required. , As for perylene, the exchange energy J that serves as an energetic barrier between the T and S states is relatively large (ca.…”
Section: Resultsmentioning
confidence: 81%
“…We will briefly discuss the reason for the decrease in τ T as the motions of the molecules become more allowed. First, self-quenching (T 1 + S 0 → S 0 + S 0 ) among perylene molecules is not responsible for this behavior, and this is based on our experimental confirmation of τ T being independent of perylene concentration (Figure S6 in the Supporting Information). Generally, for a molecule to change its electronic spin state, a fluctuating time-dependent magnetic perturbation at the position of the molecule is required. , As for perylene, the exchange energy J that serves as an energetic barrier between the T and S states is relatively large (ca.…”
Section: Resultsmentioning
confidence: 81%
“…[2][3][4][5][6] Ionic liquids are generally defined as organic salts with melting points below 100 1C and comprised entirely of ions. [13][14][15][16] The alkyl side chain length has an influence on the supramolecular assemblies and aggregation effects between alkyl tails may lead to an ordered local environment. The most extensively studied ionic liquids are the 1-alkyl-3-methylimidazolium salts.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers suggested that imidazolium-based ionic liquids may be considered as nanostructured with polar and nonpolar regions. [13][14][15][16] The alkyl side chain length has an influence on the supramolecular assemblies and aggregation effects between alkyl tails may lead to an ordered local environment. 9,17 The physical and chemical properties of ionic liquids are tunable through the selection of their cation and anion moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids containing dissolved water may not be regarded as homogeneous solvents but have to be considered as microheterogeneous materials, where the microheterogeneity may be attributed to incomplete mixing at the molecular level. [15][16][17][18] Because ionic liquids are entirely composed of ions, ionic liquids have been utilized in the preparation of ion gels (a new class of solid state electrolytes). [19][20][21][22] The addition of gelling agents to ionic liquids occasionally leads to the gelation of ionic liquids and the gelling agents include low molecular weight gelators, nanoparticles, and block copolymers.…”
Section: Introductionmentioning
confidence: 99%